Improvements in the Diagnosis of Acute Kidney Injury - Melnikov Vyacheslav; Molitoris Bruce (Saudi Journal of Kidney Diseases and Transplantation, 2008)
Acute kidney injury (AKI) represents a wide range of heterogeneous clinical conditions with a high mortality rate. Despite improvements in our understanding of the disease processes, mortality has only marginally improved and remains unacceptably high. An additional consequence of AKI is the marked acceleration of pre-existing chronic kidney disease to end-stage renal disease. A major limitation in improving outcomes of AKI has been the lack of common standards for diagnosis and severity stratification. Serum creatinine is a late marker of kidney dysfunction and injury. Presently, no available commercial test offers diagnosis, nor the ability to stratify patients by severity of injury, early in the course of disease when therapy may be beneficial. The Acute Dialysis Quality Initiative (ADQI) group proposed a standard definition and classification system for the syndrome of acute renal failure. Based on data that even small changes of serum creatinine result in increased mortality, the Acute Kidney Injury Network (AKIN) has recently proposed modified criteria. Both staging systems emphasize changes in serum creatinine and urine output. There is also potential that a number of serum and urine bio-markers developed in preclinical studies and currently being investigated and validated, will enable the early diagnosis of AKI.